Rapid detection of Kenyan tomato leaf curl virus isolates using probe-enhanced loop-mediated isothermal amplification coupled with a modified DNA extraction method - Abigarl Ndudzo; Florence Ng’ong’a; Edith K. Avedi; Elijah M. Ateka (PLoS ONE, 2026)
Plant disease management requires sensitive and user-friendly diagnostic methods. The polymerase chain reaction (PCR) and other methods have helped diagnose diseases, but they are primarily used in high-resource settings, leaving low-resource settings without effective options. A simple probe-enhanced method for the detection of Kenyan tomato leaf curl virus (Kenyan ToLCV) isolates in host crops, including asymptomatic ones, was developed by employing loop-mediated isothermal amplification (LAMP) coupled with a rapid modified DNA extraction method. A modified alkaline polyethylene glycol (APEG) approach for sample preparation from infected tomato and chili pepper leaves was optimized for sensitivity, reproducibility, and adaptability. The modified extraction buffer contained polyethylene glycol, sodium hydroxide, polyvinylpyrrolidone, and sodium chloride. Six LAMP primers and a hybridization probe targeting the AV1 gene were designed and used for specific detection of Kenyan ToLCV isolates. Gel electrophoresis, real-time detection, and color change were used to evaluate the LAMP reaction. The probe-enhanced LAMP assay detected the virus in 2.7 minutes under optimal conditions. The analytical sensitivity reached 0.001 fg/μL of total DNA. The optimized LAMP assay was 10 6 times more sensitive than conventional gold-standard PCR and did not cross-react with other tomato-infecting viruses. The modified buffer yielded a significantly shorter time-to-positive (~4.8 minutes; p < 0.0001) compared to unmodified APEG. The probe-enhanced LAMP assay detected the virus in 50% (4/8) of asymptomatic samples. The findings suggest the application of the developed assay for phytopathological testing in resource-poor areas and for direct field detection. This assay would provide a reliable approach for rapid plant health certification and quarantine inspection.